Meme Implicature Using the Word 'Tenggelamkan' - Sela Wildaan Aulia; Nurhayati (RETORIKA: Jurnal Ilmu Bahasa, 2020)
The majority of Indonesians who are known to use social media as a means of communication and entertainment are certainly familiar with the term meme. A meme phenomenon popular is the use of the word 'tenggelamkan' at the end of the discourse popularized by Susi Pudjiastuti, the former minister of fisheries and maritime affairs. The objectives of this study are as follows: (1) to determine the language style used in memes that use the word ‘tenggelamkan’ and (2) to determine the implicature of memes using the word ‘tenggelamkan’. The data source of this research is taken from various pictures on the internet, amounting to 15 memes. The data collection used is the method capture. The research method is descriptive qualitative, the analysis used is Grice's theory of conversational maxims. The results of this study indicate the themes used in memes using the word ‘tenggelamkan’ include the themes of love, friendship, corruption, worship, and food. The use of language styles that are reflected, such as 9 memes of cynicism, 5 memes of paradox, and 1 meme of rhetoric. The implicatures of meme data using the word ‘tenggelamkan’ are as follows: satire, suggestion, satire and suggestion.